Harmonisasi Al-qur’an dan Hadist dalam Kurikulum Pendidikan Islam - Cindy salsabila guritno; Dwi Nazwa Adisti; Tiara Rahma Dani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Islamic curriculum refers to education that is based on Islamic teachings and values. This curriculum not only focuses on acquiring academic knowledge, but also incorporates Islamic religious teachings into every aspect of education. Islamic education emphasizes the importance of morality, ethics and Islamic values ​​in one's life. The Islamic curriculum also covers various subjects such as the Qur'an, Hadith, fiqh (Islamic law), aqidah (beliefs), Islamic history, and Islamic ethics. The main aim of the Islamic curriculum is to make students have strong religious knowledge, skills, and character in accordance with Islamic teachings. Therefore, in writing this article the author wants to explain the relationship between the Koran and Hadith in the Islamic education curriculum. In the process of writing articles, the author uses a method in the form of previous literature research which involves reviewing relevant articles in book journals and other reliable sources. From this research, the author can conclude that the Al-Quran and Hadith will always be in harmony when discussing education, where the main or core aim of Islamic education is to educate, shape human character and morals.